PENGGUNAAN MEDIA EDPUZZLE DAN GAME MARBEL INDONESIAN CULTURE DALAM PEMBELAJARAN PKN DI SD - ADINDA WIDIA FEBRIANTI; ERWIN RAHAYU SAPUTRA (Jurnal Ilmiah Pendidikan Guru Sekolah Dasar, 2022)
As technology and information develop, learning begins to use technology. Especially with the pandemic that has hit the whole world, learning at the elementary school level is also done online and blended, therefore student learning achievement is considered unsatisfactory. It is hoped that the use of edpuzzle media and interactive Marbel games can increase the learning achievement of PKN subjects in elementary schools. This research uses a descriptive qualitative method. The approach used in this research is a qualitative approach. the qualitative research method is a method based on the philosophy of postpositivism, used to examine the condition of natural objects, (as opposed to experimentation) where the researcher is the key instrument and uses it, while the approach used in this research is research and development (research and development). ) the development model used to produce certain products and to test the effectiveness of the product in this case learning media